(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
In the 70th anniversary of the foundation of the National Health Service (NHS), the essay aims at tackling the most important features of universalism in the granting of healthcare. Both Italy and the UK chose to adopt a public health service based on the principle of solidarity and equity in access to services. In England, a deep reform has profoundly changed the face of the NHS, bringing market into health services. After analysing the criticalities of the 2012 Act, the article addresses the problems that Brexit will signify for the granting of services within the NHS. The paper concludes suggesting that the enforcement of the principle of solidarity, in the light of Sir William Beveridge’s original project could serve the scope to help the NHS to face the sustainability crisis it is passing through.